Średniowieczne nadania odpustów dla Wieliczki = Medieval Granting of Indulgences for Wieliczka - Szymborski, Wiktor (Studia religiologica, 2010)
The aim of this article was to show the medieval indulgences granted to churches, guilds and the hospital functioning in the town of Wieliczka. To this end all the indulgences granted in the area of Małopolska (Lesser Poland) starting from the 13th century and until 1525 were charted. A comparative analysis of the entire source material collated revealed that Wieliczka was one of the few places on the map of medieval Małopolska which figured highest in terms of numbers of indulgences granted. The first indulgences given to Wieliczka date back to the 14th century. Among 92 granted for the whole of Małopolska, Wieliczka received some seven. In comparison Krakow received 34 at this time, Kazimierz 10, but the Cistercian Monastery in Mogiła, at the time a rapidly developing religious centre, only gained four. In the next century the processes begun in the 14th century intensified. For the whole of Małopolska at this time 327 indulgence documents were issued to 78 centres, of which 13 or 14 concerned Wieliczka. The fact that some of these mentions do not have a date of issue and can be ascribed to ordinaries of the diocese living in both the 14th and the 15th centuries means that it is difficult to state this number equivocally. It is important to emphasise particularly that the largest number of indulgences granted to the congregation residing in Wieliczka concerned the fraternity which functioned there. The first indulgence document for Wieliczka was also the fi rst document to award with an indulgence the faithful participating in brothers’ masses and supporting the fraternity financially. The Wieliczka fraternity received five indulgences in a space of just 23 years, which is testimony to their rich development as well as the fact that its members were making concerted efforts to receive further indulgences. The inhabitants of Wieliczka were able to gain the graces of an indulgence not only by participating in the brothers’ masses but also by supporting the paupers staying in the hospital which had been founded in the 14th century by King Casimir III the Great.